2002
DOI: 10.1139/b01-137
|View full text |Cite
|
Sign up to set email alerts
|

Red/far-red light mediated stem elongation and anthocyanin accumulation in Stellaria longipes: differential response of alpine and prairie ecotypes

Abstract: We compared the stem elongation response and anthocyanin accumulation between alpine and prairie plants of Stellaria longipes Goldie under different red/far-red light ratios (R/FR) of 0.7 and 1.9 while all other environmental conditions were uniform. Both ecotypes responded to light quality. The prairie ecotype, considered to be the shade avoider, showed greater stem elongation in response to low R/FR (0.7) than under high R/FR (1.9) as compared with the alpine ecotype. The levels of anthocyanin in prairie pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 48 publications
(48 reference statements)
3
34
1
3
Order By: Relevance
“…We first subjected the plants to low R/FR conditions. This is an early neighbor detection signal, and our results confirmed previous studies of contrasting responses for the two ecotypes (Alokam et al, 2002). The alpine plants were not responsive to low R/FR and grew at rates similar to the plants grown under control light conditions (Figs.…”
Section: Shade Signals Induced Different Growth Responses In the Alpisupporting
confidence: 91%
See 1 more Smart Citation
“…We first subjected the plants to low R/FR conditions. This is an early neighbor detection signal, and our results confirmed previous studies of contrasting responses for the two ecotypes (Alokam et al, 2002). The alpine plants were not responsive to low R/FR and grew at rates similar to the plants grown under control light conditions (Figs.…”
Section: Shade Signals Induced Different Growth Responses In the Alpisupporting
confidence: 91%
“…Consequently, its tall phenotype ensures a better chance of survival among the competing neighbors (Macdonald et al, 1988). Previous studies have shown that while the alpine ecotype is nonresponsive to low R/FR, an early shade signal, the prairie ecotype exhibits a typical shade avoidance response under similar conditions (Alokam et al, 2002). Differences within the same species in response to the same cue reflect the specialization of each ecotype to its specific habitat.…”
mentioning
confidence: 99%
“…Light is one of the main determinants of anthocyanin production, and anthocyanin biosynthesis is strongly dependent on light intensity or light quality (Giusti and Wrolstad, 2005;Keppler and Humpf, 2005). In particular, when the different ecotypes were kept at different R/FR ratios, the anthocyanin level was significantly increased under higher R/FR ratios, and the pigment levels were almost the same under low R/FR ratios (Alokam et al, 2002). In our study, anthocyanin content was significantly increased in 24 ~33% with supplemental red and mixed red light treatments.…”
Section: Discussionmentioning
confidence: 99%
“…A prairie ecotype is naturally subjected to crowding in its native dense grasslands, whereas a dwarfed alpine ecotype grows in alpine regions of the Rocky Mountains with very little vegetation in which above-ground competition is almost absent. It was shown 17,105 that there is a clear variation in response to different light signals, between the two ecotypes (Fig. 3).…”
Section: Adaptive Value Of the Sas In An Ecological Contextmentioning
confidence: 93%